Adaptive laboratory evolution of Pseudomonas putida and Corynebacterium glutamicum to enhance anthranilate tolerance. Issue 11 (23rd November 2020) - Kuepper, Jannis; Otto, Maike; Dickler, Jasmin; Behnken, Swantje; Magnus, Jorgen; Jäger, Gernot; Blank, Lars M.; Wierckx, Nick
Abstract : Microbial bioproduction of the aromatic acid anthranilate ( ortho -aminobenzoate) has the potential to replace its current, environmentally demanding production process. The host organism employed for such a process needs to fulfil certain demands to achieve industrially relevant product levels. As anthranilate is toxic for microorganisms, the use of particularly robust production hosts can overcome issues from product inhibition. The microorganisms Corynebacterium glutamicum and Pseudomonas putida are known for high tolerance towards a variety of chemicals and could serve as promising platform strains. In this study, the resistance of both wild-type strains towards anthranilate was assessed. To further enhance their native tolerance, adaptive laboratory evolution (ALE) was applied. Sequential batch fermentation processes were developed, adapted to the cultivation demands for C. glutamicum and P. putida, to enable long-term cultivation in the presence of anthranilate. Isolation and analysis of single mutants revealed phenotypes with improved growth behaviour in the presence of anthranilate for both strains. The characterization and improvement of both potential hosts provide an important basis for further process optimization and will aid the establishment of an industrially competitive method for microbial synthesis of anthranilate.